Prediction of power output at different running velocities through the two-point method with the Stryd™ power meter - Garcia-Pinillos, F.; Latorre-Román, P. A.; Roche-Seruendo, L. E.; Garcia-Ramos, A. (Gait and Posture, 2020)
Background: The force- and power-velocity (F-V and P-V, respectively) relationships have been extensively studied in recent years. However, its use and application in endurance running events is limited.